Паретооптимизация параметров тренажера-гексапода по критериям маневренности - Яглинский, Виктор Петрович; Козерацкий, Геннадий Владимирович; Хихловский, Анатолий Брониславович; Озернюк, Олег Тимофеевич (НТУ "ХПИ", 2018)
Для тщательной подготовки экипажа мобильных транспортных объектов по принятию быстрых решений по удержанию курса и мгновенных реакций по изменению движения предложено усовершенствовать тренажерную технологию путем эффективного использования рабочей зоны и снижения риска возникновения сингулярных конфигураций механизма тренажера. Предложены новые методы оценки свойства "маневренность" механизма параллельной структуры и кинематики типа гексапод в виде критериев эффективности рабочей зоны и сингулярности конфигураций. В результате Паретооптимизации критериальных показателей определена область оптимальных значений отношения радиусов ориентации шарниров платформы гексапда в интервале 0,75…0,95. Установлено, что конструктивные размеры авиатренажера модели Ан 124-100-D АНТК "Антонов" расположены в оптимальной области. Рекомендуемый диапазон значений углов тангажа (от 20º до 50º) позволяет эффективно использовать рабочую зону тренажера при одновременном снижении риска возникновения сингулярных конфигураций.

To carefully prepare the crew of mobile transport facilities to make quick decisions on course retention and instant reactions to changing traffic, it is proposed to improve the training technology by effectively using the work area and reducing the risk of the occurrence of singular configurations of the simulator mechanism. is necessary. New methods for estimating the property of the "maneuverability" of the mechanism of parallel structure and kinematics of the hexapod type in the form of criteria for the efficiency of the working zone and the singularity of configurations are proposed. As a result of the analysis of known studies of singularity it is established that the singularity is a special kind of configuration in which the intrinsic rigidity of the hexapod mechanism is lost or there are uncontrollable degrees of freedom, which leads to loss of controllability. The singularity of the direct kinematics arises under the condition that the Jacobi matrix has rank less than 6 (not full rank). Physically this kind of singularity arises if two or three bars are parallel to each other, or three rods are located in a common plane. In such cases, the platform receives an additional one or more degrees of freedom, even if all the drives are locked. In order to avoid the singularity in this case, it is recommended to increase the rigidity of the mechanism by tilting two or three bars (to establish them not parallel to each other). The singularity of the inverse kinematics of mechanism arises if the direction of one or more bars is perpendicular to the axial directions of the drive hinges (for hexaglides). In this situation, the platform loses one or more degrees of freedom and there is uncontrollability in the form of ambiguity of continued movements or the rigidity of the hexapod mechanism increases dramatically. The singularity of the direct dynamics arises under the condition that the two rods are located along one line and all the actuators except these two are blocked. In this case, the power locking mechanism occurs and the mechanism can remain in equilibrium with any significant forces in the drives (the mechanism loses two degrees of freedom). Singularity of the reverse dynamics arises under the condition that the drives are blocked, and the mechanism still has one degree of freedom. In this case, the mechanism acquires the so-called quasi-zero and negative rigidity for the resemblance of the elastic Mises systems. As a result of Paretooptimization criterial indicators, the range of optimal values of the ratio of the radii of orientation of the hinges of the hexagon platform in the range 0.75...0.95 is determined. It is established that the design dimensions of the airplane simulator on model AN 124-100-D ANTK "Antonov" are located in the optimal area. The recommended range of angular pitch values (from 20º to 50º) allows efficient use of the working area of the simulator while reducing the risk of singular configurations.
Pareto-optimization of parameters of the simulator-hexapode on the criteria of maneuverability
Keywords: авиасимулятор полноуправляемый; платформа Стьюарда; ориентация; матрица Якоби; жесткость; Full Flight Simulator; Steward platform; orientation; Jacobi matrix; rigidity